Islamic ethical values on bioengineering practices : issues in genetic engineering - Shuriye, Abdi Omar (Research Centre, International Islamic University Malaysia, 2006)
Bioethics as a field of study in the hierarchy of disciplines in ethical studies and human knowledge has emerged in early 1950s as a result of the expansion of scientific and technological innovations. The term bioethics was first used by biologist Van Rensselaer Potter with the intention to coin a term for the new field related to human survival, bioethics. The term however transformed with time to denote broad landscape of the moral problems of life sciences. Bioethics, without doubt, is currently regarded as sweeping transformation of the early domains, such as medical ethics; which refers to the moral obligations of the physicians. Divergent as it is, to medical ethics, bioethics raises questions on human life, death, dignity, creativity, role of God in human innovation and moral values, standards and professional practices. It denotes the crossroads of ethics and life science. Due to the seriousity of the field however, it became extremely relevant in all academic discussions related to science and technology. In fact, it is an influential political force in modern governments. Though it has emerged in the face of great changes in science and technology it commands key terms in the decision-making of environment, public policy and educational systems, as it focuses on human values. It attempts to find answers to the dilemmas that physicians had to confront at the bedside of dying patients, public choices faced by lawyers, and issues on environmental policies. Even if we agree with old notion that, bioethics deals with life sciences, it is understood that today’s life sciences can no longer be assumed as a narrow discipline as it was portrayed in the past, as contemporary nature of the subject covers human life, behaviour and the natural spheres. Put differently, the subject of bioethics is no longer limited to biological and medical sciences. This research is about moral beliefs on bioengineering ethics and practices, a subject that have developed over the years of human existence. Moral philosophy is related to human life, good, bad, judgment, happiness and justice, objectivity of right and wrong or normativeness of ethical issues; the concern to develop rational principles and guiding standards according to which humans should live, or the rational evaluation statements. Ethical studies are of diverse. In some aspects they evaluate and characterize the meaning of ethical terms, a branch of ethics that ethicists termed metaethics. Other part of it deals with how people actually behave; this branch is referred to by the ethicists as descriptive. Most ethical theories are teleological, promoting the idea that actions are moral, provided that they target moral goal. Moral theories on the other hand are motivated by certain intrinsic intentions. Ethic is related to religion as well as to rationality. Socrates (470-399 B.C.) started the pursuit of ethics from rational perspective. Little is known about Socrates’ works on ethics without referring to Plato (428-348 B.C.), student of Socrates. Plato’s early thought is regarded representative of Socrate’s view and from him we know that Socrates was concerned with the character of moral virtues. However, the study on moral virtues by Socrates was mainly an endeavour based on rational judgment without employing faith or traditional beliefs. Plato’s approach is similar to that of his teacher, as the theory of reality became the bases for his ethical studies. The theory of forms described morality and ethics as the form or the idea of eternal and static structure. Morality, according to Plato, therefore, falls under these structures, and it becomes knowledge as moral people are wise, just, rational, courageous, moderate and harmonious with their soul. Ethicists refer to Aristotle (384-322 B.C.) as one who drew distinction between him and Plato as he based morality or human nature. Meeting the needs or achieving happiness, the ultimate goal for life, is the purpose of ethics for Aristotle. To achieve happiness, however, requires following some structured guidelines through reasoning, as a rational person adheres to some traits to maintain or achieve happiness. Epicureanism, an early school of moral philosophy, which was developed after the demise of Aristotle, is worth mentioning in this regard. Epicurus (341-270 B.C.) the founder of what later to be known as Epicureanism, believed that the highest good is to avoid pain and pursue pleasure. Another ethicist school of the same period, the Stoicism, advocated control of the emotions as the highest level of moral standards. After the emergence of Christianity however, the literature on ethics, methods and approaches of study took diverse directions. God became the ultimate reality in the mind of the many ethicists and scholars formulated new methods and trends. As the purpose of life in Christianity is to rule the earth on moral grounds, and not merely attaining world pleasure, which is a religious message, St. Augustine (354-430 A.D) spearheaded the trend of Christian moral harmony. Other Christian theologians include Thomas Aquinas (1225-1274 A.D.). Aquinas moral theory was based upon natural law. He contended that the ultimate good of humans is spiritual union with God. As we will see in other sections of this research, Christians accept ethical issues are part of larger scheme of revelation. In the hierarchy of contemporary Western knowledge, ethics is a branch of philosophy, and as a discipline of study it falls under the philosophy department, so in Western Worldview ethics is a philosophical field of enquiry. The systematic study of values is what ethicists call ethics; it is the study of how to live decent, as such ethicists are concerned with how to determine standards. The two terms “ethics” and “morality” become imperative at this point. These terms are interchangeable in most cases. Morality deals with code of conduct. However, authorities of the subject argue that ethics refer to system of values, while, morality connotes righthood or wronghood. That indicates the fact that ethics is concerned with the systematic study of human values including the theories of conduct and focuses on moral dimensions of human life. We shall elucidate this in the subsequent parts of this research. Moral theories evaluate moral concepts and identify the significant of their approach. Utilitarian ethicists focus on maximizing human well being as a whole. Basic approaches of utilitarianism are Act-Utilitarianism which focuses on actions, not the rule, of the individual. John Stuart Mill (1806-1873) is considered one of the advocates of Act Utilitarianism, as we will illustrate it in the related chapters. Another approach is what ethicists term it as Rule-Utilitarianism which holds that moral rules are more imperative as the ethical rules will, in its general outlook, lead to the well being of all. Duty ethics is another moral theory; an idea that our duty to behave morally becomes obligatory upon us. Right ethics theory which advocates the contention that societies have moral rights and violating it is deemed unethical is another ethical theory related to. Both Right and Duty ethics theories do not take consequences of an action or overall good of the action, into considerations. Meanwhile virtue ethics theory outlines the idea of moral distinction, traits and character-fine, emphasizing on the personality. Professional ethics refers to the moral rules that professionals should adhere to. Duties performed by engineers, for instance, are comparatively risky and could annihilate nations if ethical rules ignored. Professional duty requires extensive formal education, use of judgment and high level of skills with governing standard principles. Professional duty also comes with autonomy, knowledge, recognition and licensing or certification from a recognized bodies and authorities. Construction sector, road and rail networks, transportation systems, and environment, are only some areas that unethical professionals could contaminate it. Exposing of deadly virus by an immoral physician could cause the death of millions before it could be contained. For this raison d'être, profession requires deontological oath which makes the professional to be duty-based. Professional organizations have made the oath mandatory to set a moral stage. Nonetheless, poor services and selfish personal interest, unfortunately remains, intact. The emergency of biotechnology, as mentioned, had necessitated the implementation of bioethics rules. The first bioethical case that was officially documented immerged from in vitro fertilization (IVF) where a baby, Louise Joy was born to infertile couple, John and Lesley Brown in 1982. The Department of Health and Social Security convened a committee to deal with ethical and social implications of the technology. Other bioethical issues related to abortion and euthanasia has existed as long as in early eighteenth century. Ethical dimensions of modern organ transplantation remain one of the topics in bioengineering that need further illustration from the socio-human perspectives. In fact, it is more complex and dynamic than earlier thought, as it deals with therapeutic endeavour and pursuit. Therapeutic should not be confused with conventional therapy in the general term. Transplanting involves relocation of organs from one individual to another or within the same individual, and quickly became treatment of choice or life sustaining therapy particularly for certain types of end-stage cardiac and liver failure. The success of organ transplant triggered a high demand for the treatment to the point that there are now in the world inadequate organs for transplantation. The most comprehensive definition of organ transplantation is a “unique way to share our humanity”. A main part of organ transplant is tissue engineering, which is already having an impact on organ transplant procedures. The perception that many individuals have about organ transplant is greatly influenced by people’s perception of the relations between the self and the body. For that matter, if the body is merely instrumental to our ends then continued functioning of the body is understandably significant These introductory remarks shall mention the state of bioethics sources and the available literature. Divine sources remain imperative. From Islamic point of view, for instance, the Qur’an is the first source of bioethics but this would not mean that this divine document tells all about issues related to biotechnology and bioethics. Reason and social environment are other sources of bioethics both from Islamic and Western perspectives. On the literature, available on the subject, one finds few specialized works in the field. Islamic Ethics for Life edited by Jonathan E. Brockopp is one of the few volumes in which the author deliberated how Islam addressed the sacredness of human life. The book consists of articles on war, abortion, and euthanasia. The authors debated those issues from the perspective of Islamic jurisprudence. Islamic Medical Ethics in the Twentieth Century by Vardit Risplen-Chaim contains general study of contemporary Islamic medical ethics. The author investigates several related topics including Artificial Insemination, Organ transplant, Abortion, and Euthanasia. The book is fatwa-based; in the sense that the author employs more fatwas than the other sources. Biomedical Issues: Islamic Perspective by Abul Fadl Mohsin Ebrahim is one of the works in English on the topic, written by a Muslim scholar. The work covers various issues in biomedical sciences and problems of infertility. Majdah zawawi’s Human Cloning is a inclusive study on Human Cloning from legal and ethical perspectives, originally a chapter in the author’s MCL dissertation, the work is a constructive manuscript on cloning. Ahmad Salamah’s Atfal al-Anabib baina al-‘Ilm wa ash-Shari‘ah is a general outlook on family planning causes of sexual impotent and problems of pregnancy, concentrating on the legal aspect of the subject. The Institute of Islamic Understanding Malaysia (IKIM) had remarkably ventured into the subject, through organizing conferences and publications. The institute published more than four books on related issues and held several seminars directly or indirectly rated to the ethics of technology and biosciences. Bioethics: Ethics in the Biotechnology Century edited by Abu Bakr Abdul Majeed is one of the publications of IKIM. This book contains papers presented at international conference organized by the institute in 2001. The institute also published Islam, Science and Technology edited by Anwar Ab Razak and Abu Bakr Abdul Majeed. This research contains few chapters. Chapter one of this research deals with the origin and the nature of ethics, status of Islamic ethics, professionalism and the relationship between law, religion and ethics are other aspects discussed in this chapter, while chapter two is an attempt to evaluate moral theories, including Utilitarianism and egoism. Chapter three however, investigates the scope, origin and history of bioengineering practices. Ethical and religious dimension of human cloning is the task of chapter four, which provides diverse perspectives from the Qur’an, advocates and opponents views of cloning, and socio-ethical implications. Chapter five focuses organ transplant from Islamic perspective. Meanwhile, techniques in genetic engineering and ethical concerns on productivity and fertility are some issues discussed in chapter Six. Meanwhile protection of foetus, methods of aborting and personhood of foetus from Qur’anic and ethical perspectives are some themes treated by chapter seven. Chapter Eight critically measures mercy death, the requisites and ethical dimensions.